2013
DOI: 10.1104/pp.112.211029
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic Peptide Technology for Functional Dissection ofCLV3/ESRGenes in Arabidopsis      

Abstract: In recent years, peptide hormones have been recognized as important signal molecules in plants. Genetic characterization of such peptides is challenging since they are usually encoded by small genes. As a proof of concept, we used the wellcharacterized stem cell-restricting CLAVATA3 (CLV3) to develop an antagonistic peptide technology by transformations of wild-type Arabidopsis (Arabidopsis thaliana) with constructs carrying the full-length CLV3 with every residue in the peptidecoding region replaced, one at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…The amino acid at position 6 of CLE peptides is crucial for their activity (15), and indeed, replacement of the corresponding glycine by threonine yielded a CLE45 variant (CLE45 G6T ) that had identical effects as the wild-type version but required application of higher peptide concentrations (Fig. 1K).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid at position 6 of CLE peptides is crucial for their activity (15), and indeed, replacement of the corresponding glycine by threonine yielded a CLE45 variant (CLE45 G6T ) that had identical effects as the wild-type version but required application of higher peptide concentrations (Fig. 1K).…”
Section: Resultsmentioning
confidence: 99%
“…The jhs1 mutant plants were crossed with wild-type transgenic plants carrying ProWUS:GUS, ProCLV3:GUS, or ProSTM:GUS (Angela et al, 2002;Meng et al, 2012;Song et al, 2013), respectively. F 3 plants homozygous for the reporter gene and jhs1 were selected.…”
Section: Expression Pattern Analysis Of Sam-specific Genesmentioning
confidence: 99%
“…In addition, previous studies revealed that T-DNA insertion mutants of CLE1, CLE7, CLE10, CLE16, CLE18, or CLE19 in Arabidopsis exhibited no visible abnormal phenotype (Fiers et al, 2004;Jun et al, 2010), but overexpression of the CLE genes CLE2, CLE3, CLE4, CLE5, CLE6, CLE7, CLE10, CLE11, and CLE13 resulted in pleiotropic phenotypes similar to those of CLV3 or CLE40 overexpression plants, and in vitro application or overexpression of one of the CLE genes CLE19, CLE21, CLE25, CLE42, and CLE44 caused similar dwarf and short-root phenotypes (Fiers et al, 2004(Fiers et al, , 2005Strabala et al, 2006), suggesting a high level of functional redundancy or overlap among CLE members. Fortunately, an antagonistic peptide technology (Song et al, 2013) was developed recently as an effective tool to investigate the endogenous functions of these functionally redundant secreted peptides. Using CLV3 as a test case, Song et al (2013) examined the antagonistic peptide technology by transformations of wild-type Arabidopsis with constructs carrying the full-length CLV3 with every residue in the peptide-coding region replaced one at a time by Ala to probe the effectiveness of each mutation.…”
mentioning
confidence: 99%
“…Fortunately, an antagonistic peptide technology (Song et al, 2013) was developed recently as an effective tool to investigate the endogenous functions of these functionally redundant secreted peptides. Using CLV3 as a test case, Song et al (2013) examined the antagonistic peptide technology by transformations of wild-type Arabidopsis with constructs carrying the full-length CLV3 with every residue in the peptide-coding region replaced one at a time by Ala to probe the effectiveness of each mutation. They found that the Gly-to-Ala substitution in the core CLE motif caused a dominant-negative (DN) clv3-2-like phenotype.…”
mentioning
confidence: 99%
See 1 more Smart Citation